MiR-34b regulates cervical cancer cell proliferation and apoptosis - Zhen Cao; Gong Zhang; Conghua Xie; Yunfeng Zhou (Artificial Cells, Nanomedicine, and Biotechnology, 2019)
Objectives MiR-34b is a tumour suppressor in different kinds of carcinomas. This study investigated the role of miR-34b in proliferation and apoptosis of cervical cancer.Materials and methods The expression of miR-34b in 60 cervical cancer patients were quantified by RT-PCR and correlated with their clinicopathological parameters. Besides, there is a significant reverse relationship between miR-43b and TGF-β1 expression in tumour tissues. Cell proliferation and apoptosis was detected by CCK-8 assays and flow cytometry in cell lines transfected with miR-34b mimics. Western blotting, quantitative reverse transcription-PCR (RT-PCR) and luciferase assays were conducted to analyze the regulation of TGF-β1 by miR-34b in cell lines.Results Here, we found expression of miR-34b to be downregulated in cervical cancer in comparison with the adjacent normal tissues. Expression levels of miR-34b were associated with enhanced malignant potential, such as tumour stage and stromal invasion. The overexpression of miR-34b potently suppressed cell proliferation and induced the apoptosis of cell lines.Conclusions MiR-34b and TGF-β1 contribute to cervical cancer cell proliferation and apoptosis and are potential targets for cervical cancer therapeutics.